Mitigating Product Shortage Due to Disruptions in Multi‐Stage Supply Chains. Issue 4 (4th December 2020) - Lücker, Florian; Chopra, Sunil; Seifert, Ralf W.
Abstract : We focus on the optimal use of risk mitigation inventory (RMI) and reserve capacity to manage disruption risk in serial multi‐stage supply chains where product transformation occurs at each stage. We find that under reasonable conditions it is better to hold more RMI downstream than upstream even when the upstream holding costs are lower. We also find that it is often optimal to hold more reserve capacity downstream than upstream. While in one‐stage supply chains RMI and reserve capacity always behave as substitutes, it turns out that in multi‐stage serial supply chains the interplay between RMI and reserve capacity is more nuanced. We find that echelon RMI and reserve capacity at each stage are substitutes. In contrast, RMI at a stage complements reserve capacity at the adjacent downstream stage.